Managing and optimizing the output performances of a triboelectric nanogenerator by a self-powered electrostatic vibrator switch. (April 2018) - Yang, Junjie; Yang, Feng; Zhao, Lei; Shang, Wanyu; Qin, Huaifang; Wang, Shujie; Jiang, Xiaohong; Cheng, Gang; Du, Zuliang
Abstract: Using a switch is an effective strategy for managing and improving the output performances of a triboelectric nanogenerator (TENG). However, the previous switches designed for the TENGs are triggered by external mechanical motion or integrated circuits, which increase the complexity and fabrication cost of the TENG. In this article, a TENG system with a self-powered switch has been established by using an electrostatic vibrator switch, in which the switch's vibrating is driven by the potential difference of the TENG itself. In a sliding mode TENG, its output properties can be regulated and improved by the vibrating frequency of the switch, which can be adjusted by the switch's length. Compared with the same TENG without a switch, its instantaneous output power and total output energy for a load resistance of 0.1 MΩ are increased by 1.8 × 10 7 and 4.7 × 10 3 times, respectively. In a rotation disk TENG, its maximized output voltage and output energy can be achieved, as the switch's vibrating frequency is adjusted to two times the TENG's frequency. Because of the excellent impedance matching ability of the TENG with a vibrator switch, it can be combined with a transformer to form a power management system, which is verified to have better powering abilities as charging a capacitor and lighting a quantum dot light-emitting diode. The self-powered vibrator switch demonstrated here has promising applications in enhancing TENG's output performances and developing power management circuit. Graphical abstract: An electrostatic vibrator switch has been introduced as a self-powered switch of a triboelectric nanogenerator (TENG), where its vibrating is driven by the potential difference of the TENG itself. Using this switch, the output voltage and output energy of the TENG can be maximized. Also, a circuit with enhanced powering ability for a capacitor and a QLED has been developed based on the self-powered switch.fx1 Highlights: A self-powered electrostatic vibrator switch for a TENG is designed and fabricated. With the switch, the TNEG's power peak and output energy are largely increased. The output energy can be maximized by tuning the switch's vibrating frequency. The powering abilities for a capacitor and a QLED is largely enhanced.